Assessing the effects of past and future land cover changes in ecosystem services, disservices and biodiversity: A case study in Barranquilla Metropolitan Area (BMA), Colombia - Juanita, Aldana-Domínguez; Ignacio, Palomo; Jorgelina, Gutiérrez-Angonese; Cecilia, Arnaiz-Schmitz; Carlos, Montes; Francisco, Narvaez (Ecosystem services, 2019)
•The Barranquilla Metropolitan Area showed rapid land cover changes and ecosystem degradation during the last decades.•Land cover changes have diminished the supply of provisioning and regulating ES and increased EdS.•We evaluated potential impacts of land use planning in ES, EdS and biodiversity.•Projected urban expansion will degrade important areas for biodiversity and ES.•Land use planning must consider ES, EdS and biodiversity to avoid ecosystems degradation. Urbanization is one of the most important drivers of change worldwide, with the fastest pace happening in Latin America, impacting negatively on biodiversity and ecosystem services (ES). In this study we evaluated the effects of past and future land cover changes in ES, ecosystem disservices (EdS) and biodiversity, in a case study in the Barranquilla Metropolitan Area (BMA), Colombia. First, we estimated ES supply and demand and EdS associated to different land covers. Then, we evaluated land cover changes across time and their impacts on ES and EdS. Finally, we reviewed the Territorial Ordering Plans (POT) to evaluate where urbanization is planned for the year 2027, and assessed the potential impacts of such POT on biodiversity and ES. We found that natural areas have diminished, resulting in the decrease of provisioning and regulating services and the increase in EdS. Urban expansion is contributing to the degradation of ES. We argue that this study contributes to understand the effects of land cover changes on biodiversity, ES and EdS around a Latin American metropolitan area, where this kind of studies are still scarce. We present broader lessons on how ES science can improve land use planning instruments.